KALIMAT INTEROGATIF BAHASA BATAK TOBA DALAM TURI-TURIAN NI SI JONAHA - Saragi, Wandy; Faizah AR, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe interogative sentences of Batak Toba language which includes (1) types of interogative sentences, (2) markers of interogative sentences. This research is a descriptive research. The subject of this study is the Turi-turian text of Ni Si Jonaha. The object of this study is the interogative sentences contained in Turi-turian Ni Si Jonaha. Data of this study were obtained by reading and recording techniques. The data were analyzed by (1) classifying them based on types and markers of the interrogative sentences (2) analyzing them with reference to the theory used in accordance with the synthesis (3) describing and interpreting them based on the research findings, and (4) writing a report on analysis findings called a project paper. The research findings are as follows; (1) interrogative sentences ask for recognition of "olo" (yes) or "indaong" (not), or "olo" (yes) or "inda" (not) responses. Markers of this type of interrogative sentences include: (a) intonation-categorized markers and (b) grammatical marker by adding do particle (2) interrogative sentences ask for one of sentence elements. The markers of this type of interrogative sentences are lexical markers with the question words: (aha aha ma, aha do, he, ise, dia, sadia, and andigan) (3) interrogative sentences ask for 'alasan' (reasoning). The marker of interrogative sentence of this type are lexical markers in the form of question words: beasa or boasa (4) interrogative sentences ask for an answer in the form of an opinion (regarding the question asked). The interrogative sentence marker of this type is a lexical marker in the form of a question word: beha (5) Interrogative sentences that present interrogative sentence markers of this type are lexical markers with a negative word form: so or inda followed by a statement.Keywords: Interrogative Sentence, Marker, Turi-turian Ni Si Jonaha, Batak Toba Language